2019
DOI: 10.2514/1.j057850
|View full text |Cite
|
Sign up to set email alerts
|

Wall-Resolved Large-Eddy Simulations of Transonic Shock-Induced Flow Separation

Abstract: This paper reports the wall-resolved large eddy simulations of shock-induced boundary layer separation over an axisymmetric bump for a flow Mach number of 0.875 and a chord-based Reynolds number of 2.763 million. The incoming boundary layer has a momentum-thickness Reynolds number of 6600 at one and a half chord lengths upstream of the leading edge. The calculations simulate the experiment by Bachalo and Johnson (AIAA Journal, Vol. 24, No. 3, 1986), except that the tunnel walls are ignored and the simulations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(5 citation statements)
references
References 54 publications
0
5
0
Order By: Relevance
“…In contrast, the CES-KOS model provides the highest accuracy regarding the estimation of the separation length, with an error of only ≈4%. Figure 19 shows in its first row streamwise velocity profiles obtained by CES-KOS, WMLES [41], and WRLES [42]. It may be seen that the CES-KOS model predicts the streamwise velocity more accurately than WMLES and WRLES.…”
Section: Ces-kos Vs Wmles and Wrlesmentioning
confidence: 99%
See 2 more Smart Citations
“…In contrast, the CES-KOS model provides the highest accuracy regarding the estimation of the separation length, with an error of only ≈4%. Figure 19 shows in its first row streamwise velocity profiles obtained by CES-KOS, WMLES [41], and WRLES [42]. It may be seen that the CES-KOS model predicts the streamwise velocity more accurately than WMLES and WRLES.…”
Section: Ces-kos Vs Wmles and Wrlesmentioning
confidence: 99%
“…Figure 19. CES-KOS vs. LES-type WRLES [42] and WMLES [41] models: Profiles of the normalized streamwise velocity ⟨U⟩/U re f , Reynolds stress ⟨uv⟩/U 2 re f , pressure, and skin-friction coefficients at different locations.…”
Section: Ces-kos Vs Wmles and Wrlesmentioning
confidence: 99%
See 1 more Smart Citation
“…Tian et al [34] numerically investigated the jet and shock waves generated by near-wall bubble. Based on the numerical schlieren method, which is also used to show the flow as well as the turbulent structure [35] , [36] , [37] , when the jet impinges on the wall, the shear flow will tear the toroidal bubble and generate two toroidal shock waves. Zevnik and Dular [27] conducted a numerical study of a cavitation bubble near a rigid particle.…”
Section: Introductionmentioning
confidence: 99%
“…Liu et al [15] found that the jet induces a first peak at the center of the wall and a second peak at high pressure inside the bubble, based on the front tracking method. Based on numerical schlieren (which also visualize turbulent structures [16,17]), Tian et al [18] state that the shock wave causes the first pressure peak, and the jet causes the second pressure peak. Sun et al [19] reported that the rigid wall with a gas entrapping hole can reduce the pressure of the jet on the wall.…”
Section: Introductionmentioning
confidence: 99%